The effect of hyaluronic acid gel on preventing post-surgical adhesions after laparoscopic surgery (International Journal of Scientific Research and Management (IJSRM), 2018)
Intraperitoneal adhesions are an important cause of postoperative intestinal obstruction, abdominal discomfort, and infertility. Despite careful attention to minimize tissue trauma and ensure hemostasis, pelvic surgery is associated with both de novo adhesion formation and reformation. In this study our aim is to investigate the efficacy of hyaluronic acid gel on preventing/healing postoperative adhesions. 124 women on reproductive age who underwent emergency laparoscopic surgery (appendicitis, gynecologic emergencies, trauma, hernias ) included in this retrospective study. 28 of these patients underwent second-look surgery in 14-30 days. 17 of patients were applied hyaluronic acid gel on the initial surgery (Group-1) and 11 of patients were not appiled (Group-2). There were no signiﬁcant differences between the two groups for age and weight. The operating time was similar in the two groups. At follow-up, a signiﬁcantly (p<0.01) lower rate of postsurgical adhesions was observed in Group-1 in comparison with Group-2. The median rate of adhesions was signiﬁcantly (p<0.05) lower in patients treated with hyaluronic acid in respect to the group who treated surgery alone. This study showed that hyaluronic acid treatment after laparospopy/laparotomy is a significantly effective and very cost-effective option for prevention and treatment of postoperative adhesions. We believe it is very important of usage hyaluronic acid especially on reproductive age women population in order to prevent the worsening effect of postsurgical adhesion on fertility.